Formulation and Evaluation of Atenolol Orodispersible Tablets - Mohammed Mahboob Shareef; Ruhi Anjum; Prasanthi D (Asian Journal of Pharmaceutical Research and Development, 2024)
The main objective of this study was to prepare and evaluate fast dissolving tablets of Atenolol using three different types of superdisintegrants. Various formulations were prepared by direct compression using different concentrations of superdisintegrant i.e. namely Kyron T-104, Kyron T-154 and Kyron T-314. The compatibility studies between drug and excipients were carried out using FTIR spectroscopy. The blend was evaluated for additive properties. The tablets were evaluated for physical properties and in vitro drug release. From this study formulation containing Kyron T-154 was found to possess better disintegration time of 15 secs, water absorption ratio (77.5 %), and wetting time (22.7 sec) with taste masking property at low concentration. An accelerated stability study on optimized formulation was performed as per ICH guidelines. It was found to be stable, with insignificant changes in the hardness, disintegration time, and in-vitro drug release pattern.